Vice to virtue: intracellular biogenic nanoparticles for the generation of carbon supported catalysts - Vijayakumar, P. S.; Selvakumar, S.; Gholap, Ramkrishna S.; Singh, A. P.; Bhagavatula L. V. Prasad (Journal of Nanoscience and Nanotechnology, 2010)
Intracellular biogenic nanoparticles are considered disadvantageous as the separation of the nanoparticles from the biomass becomes intricate. However realizing the importance of carbon supported catalyst for many important organic reactions we envisaged these nanoparticles as a source for carbon supported catalyst. Herein we demonstrate the heat treatment of intracellular biogenic nanoparticles under inert atmosphere as an efficient method for the preparation of carbon supported metal oxide catalysts. Aspergillus ochraceus, a fungus isolated from foundries, on incubation with K(2)TiF(6) led to the synthesis of intracellular titanium oxide nanoparticles. The nanoparticles embedded biomass upon heat treatment at 600 degrees C in a nitrogen environment gave titanium oxide nanoparticles implanted in a carbonaceous matrix. The material thus formed was characterized using FTIR spectroscopy, Raman spectroscopy, HRTEM and X-ray diffraction. Appreciable benzaldehyde selectivity was observed when styrene oxidation was carried out over such immobilized catalysts. The conversion rate was determined to be 76% and the benzaldehyde selectivity was greater than 80%.
Keywords: Benzaldehyde Selectivity; Biosynthesis; Carbon Supported Titania; Nanoparticles; Styrene Oxidation

Spectroscopy and catalytic activity study of gold supported on barium titanate nanotubes for styrene epoxidation - Nepak, Devadutta; Srinivas, Darbha (Applied Catalysis A-General, 2016)
Gold (0.5-5 wt.%) supported on barium titanate nanotubes (Au/BaTNT) were prepared, characterized and for the first time, investigated as catalysts for selective oxidation of styrene with oxygen (O-2 or H-2 + O-2) and peroxides (H2O2 or TBHP). Conversion of styrene enhanced when H-2 was co-added to O-2 in the reactions. Au/BaTNT activated O-2 and H-2 and produced H2O2 in situ for use in oxidations. Peroxides were found better oxidants than O-2. At optimized conditions, styrene oxide selectivity of 80.1 wt.% at styrene conversion of 60.5 wt.% was achieved over Au(1 wt.%)/BaTNT using TBHP. Au particles (5.0-7.4 nm) were dispersed and decorated on the walls of BaTNT. They exhibited superior performance to the known Au catalysts in styrene oxidation. Reactive oxygen species formed during oxidation reactions were followed with in situ spectral characterizations (diffuse reflectance UV-vis and FT -Raman). Au/BaTNT was reusable in four recycles with little loss in catalytic activity. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: Au Nanoparticles; reactive oxygen species; spectroscopy; Styrene Oxidation; Titanate nanotubes